On the rate of convergence of double series of exponents representing regular functions on products of convex polygons - Mel'nik, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Estimates exact in order are obtained in the uniform and integral metrics for the deviation of partial sums of double series of exponents that represent functions which are regular on products of convex polygons and either continuous on a product of closed polygons or belonging to the Smirnov class.